Lesson Study in an Inclusive Mathematics Classroom using Multicommunications Media: Ring Theory Course - Husniati, Andi; Akib, Irwan; Usman, Muhammad Rizal; Kristiawati, Kristiawati; Fauziyah, Nur (Jurnal Pendidikan Progresif, 2023)
Objective: This study aims to describe learning by implementing a Lesson study using multi-communication media in ring theory courses in inclusive classes of Muhammadiyah Makassar University. Methods: This study uses an experimental research design by analyzing and directly assisting students in learning. The analysis of this activity refers to planning (plan), implementation (do), and reflection (see). The subjects in this study were students of the 2017 class of Muhammadiyah Makassar University, totaling 28 students, one of whom was a deaf student. Findings: The results show that at the beginning of the performance of lesson study without video, deaf students were still less actively involved in discussing with their group friends, while in the performance of learning using multi communication media, namely in the form of learning videos accompanied by running text and sign language, deaf students seemed more active than previous learning without video media. In general, student responses to learning with the implementation of lesson study are positive. Conclusion: It is concluded that the use of multi-communication media through the implementation of lesson study has a positive impact on learning and helps students understand the material, especially students who are deaf. Keywords: lesson study, multicommunication, education inclusive.DOI: http://dx.doi.org/10.23960/jpp.v13.i2.202308